Reliability of phytoliths for reconstructing vegetation dynamics in northern temperate forest regions: A case study in northeast China. (1st December 2018) - Gao, Guizai; Jie, Dongmei; Li, Dehui; Li, Nannan; Liu, Lidan; Liu, Hongyan; Shi, Jichen; Leng, Chengcheng; Wang, Jiangyong; Liu, Baojian; Li, Ping
Abstract: Phytolith records have provided a new perspective on the reconstruction and interpretation of palaeovegetation in forested regions. However, the reliability of phytolith records for vegetation reconstruction in northern temperate forest regions has not been fully determined, and it needs to be assessed before they can be used in palaeoecological contexts. To address this issue, we analyzed surface soil phytolith assemblages at 108 sites and established a modern soil phytolith reference database for five dominant vegetation communities in Northeast China. The phytolith reference dataset was then used to analyze a stratigraphic sequence of fossil phytolith assemblages from the same region to confirm the reliability of the phytolith-based paleovegetation reconstruction. The results demonstrate that both the phytolith assemblages of surface soils and the phytolith indices (Iw, Ic, Iph and W/G) vary substantially in different temperate forest habitats, and the indices are also well correlated with the vegetation inventory data. Thus, we conclude that modern soil phytoliths are reliable analogues for reconstructing paleovegetation. The modern phytolith reference-based paleovegetation reconstruction indicates that the study area has experienced substantial vegetation change since the late-glacial. The vegetation types ranged from open Larix mixed forest to open woodland, to closed broadleaf forest, and finally to closed Pinus koraiensis mixed forest. The phytolith-based vegetation types since the late-glacial are consistent with those reconstructed by a pollen record from the same stratigraphic profile, and thus our study confirms the reliability of phytolith analysis for interpreting both the entire vegetation landscape and vegetation changes in the northern temperate forest region. Moreover, fossil phytoliths also provide additional information - including the composition of grasses in the understory, changes in the proportions of C3/C4 plants, Larix abundance and tree cover density - which complements that provided by pollen analysis. Our study provides new perspectives on the reliability of phytoliths for reconstructing vegetation dynamics in the northern temperate forest region, and it provides a robust foundation for the application of phytolith analysis in the region. Highlights: Surface soil phytolith reference was established for NE China to identify different temperate forest types. Based on the modern phytolith dataset we reconstructed the paleovegetation of a peat profile since the late-glacial. Our work confirmed the reliability of phytolith-based paleovegetation reconstruction in the northern temperate forest region.